Effects of Cell Differentiation on the Phagocytic Activities of IgM+ B Cells in a Teleost Fish - Wu, Liting; Kong, Linghe; Yang, Yanjian; Bian, Xia; Wu, Siwei; Li, Bingxi; Yin, Xiaoxue; Mu, Liangliang; Li, Jun; Ye, Jianmin (Frontiers in Immunology, 2019)
Teleost B cells have phagocytic activities for ingesting particulate antigens, such as bacteria, in addition to the functional secretion of immunoglobulins (Igs). In the present study, the phagocytic activities of IgM+ B cells under various differentiational conditions residing in peripheral blood leukocytes were investigated in a teleost fish Nile tilapia (Oreochromis niloticus). The IgM+ B cells were recognized as IgMlo or IgMhi subsets based on their membrane IgM (mIgM) levels. The mIgM, secreted IgM (sIgM), major histocompatibility complex class II and reactive oxygen species were detected. Expressions of transcription factors (Pax5 and Blimp-1) and B cell signaling molecules (CD79a, CD79b, BLNK and LYN) suggested that IgMlo B cells were resembling as plasma-like cells and IgMhi resembling as naïve/mature B cells, respectively. Analysis of phagocytic activities demonstrated that both IgMlo and IgMhi B cells have a similar phagocytic ability (phagocytosis percentage); however, the phagocytic capacity [phagocytic index and the mean fluorescence intensity (MFI)] of IgMhi B cells was significantly higher than that of IgMlo B cells. Taken together, the results indicated that B cell differentiation may cause the decrease of phagocytic capacity but not phagocytic ability of phagocytic IgM+ B cells in teleost. The finding may provide an evolutionary evidence for understanding the greater specialization of the B cell in more sophisticated adaptive humoral immunity, by decreasing phagocytic activity in order to contribute its function more specifically into antibody-secreting.